Education on Utilizing Plastic Waste through Creative Class by Sikola Inspirasi Alam in 3T Area - Muzri S, Ahsan; Sakkir, Geminastiti; Saputri, Nur Eka; Karamay, Berkah Risva Yanti; Pangestu, Risha Dwi (Yayasan Ahmar Cendekia Indonesia, 2025)
Plastic waste has become a significant global problem, especially in remote areas. With limited waste management services in these regions, plastic often pollutes the environment, causing harm to health and ecosystems. This community service project, led by Sikola Inspirasi Alam, aims to educate children in the 3T regions of Gowa Regency about recycling plastic waste. Through creative classes, children learn how to turn plastic waste into useful items, like pencil cases. This initiative seeks to raise environmental awareness and teach practical skills for sustainable waste management among the younger generation. The program has shown positive results, with students gaining a better understanding of recycling and successfully creating useful products from plastic waste.